Avanços da energia eólica no Brasil : uma análise das políticas públicas e seus resultados - Santos, Luan Tolentino dos (2017)
The main objective of this study is to verify the evolution of wind energy in Brazil from the 2000s. In this sense, it was proposed to investigate which factors contributed to the expansion of the electric power generation from the wind power source in Brazil, based on the regulatory, fiscal and innovation policies that involve the sector, besides external elements and challenges that influenced its development. In this view, a exploratory-descriptive research was carried out, through bibliographical and documentary researches that contributed to the proposed study. This analysis took into account the global context of the wind power source, as well as the experience of selected Latin American countries (Chile, Uruguay, Peru and Argentina), which, like Brazil, have been highlighted in the region. From the obtained results, it was observed that among the main reasons that allowed the development of the Brazilian wind sector, it is highlighted: the creation of the Incentive Program for Alternative Energy Sources (PROINFA), which represented the kickoff for the introduction of wind power in Brazil; the changes in the structure of the Brazilian Electric Sector, which enabled the implementation of a competitive system of energy trading, the auctions; the investments in technology from 2008. Despite these advances, it was verified that Brazil was not able to develop a national industry of wind technology, since its policies had as main focus the creation of market. In this sense, important gaps have been identified, such as: (i) the lack of an favorable environment to Science and Technology; (ii) a mismatch between sectoral planning and current legislation (such as energy auctions and the absence of transmission lines); (iii) the limited supply of financing for investments in wind energy. In addition, it was verified that the reduction of wind energy prices in Brazil is mainly due to the international advance of technology and the global crisis from 2008, which attracted investors to Brazil. Finally, at the regional level, it was verified that Brazil is a leader in wind energy capacity and generation and has served as an experience for the countries of the same region.